Occupational noise exposure and hearing assessment of hydraulic fracturing workers: quiet versus conventional fleets - Blevens, Melissa S., author; Brazile, William, advisor; Tsai, Candace Su-Jung, committee member; Van Dyke, Michael, committee member; Autenrieth, Daniel, committee member; Lipsey, Tiffany, committee member (Colorado State University. Libraries, 2024)
Oil and gas extraction companies are exempt from implementing hearing conservation programs for their workers according to the Occupational Safety and Health Administration's (OSHA) noise standard. The occupational noise exposure and hearing status of these workers has not been published in scientific literature before the present study, presumably due to this exemption. In this study, area and personal noise exposures and worker hearing acuity were measured at both conventional and quiet hydraulic fracturing fleets, allowing a comparison between the fleets. Quiet fleets refer to the use of engineering controls to decrease noise levels of the pumps while conventional fleets do not employ these measures. In both fleets, the authors conducted personal noise dosimetry, equipment noise measurements, and pure tone audiometry pre- and post-work shift to determine if there were temporary threshold shifts (TTS) in hearing. Based on the personal noise dosimetry results, 42/50 (84%) of the quiet fleet and 34/34 (100%) of the conventional fleet workers sampled were at or over 100% noise dose according to the American Conference of Governmental Industrial Hygienists' (ACGIH) noise Threshold Limit Value (TLV). Based on the OSHA Permissible Exposure Limit (PEL) noise criteria, 9/50 (18%) of the quiet fleet workers and 15/34 (44.1%) of the conventional fleet workers were at or over 100% noise dose. Workers in both fleets experienced TTS, but no significant difference was observed between the types of fleets in relation to TTS. Most equipment of both fleets exceeded 85 decibels, but the pumps of the quiet fleet were ~14 dB lower than those of the conventional fleet. Although the quiet fleet noise controls reduced personal noise exposure, a portion of the quiet fleet workers sampled still faced noise levels that could increase the risk of hearing loss. The researchers suggest the initiation of a hearing conservation program despite OSHA exemption to safeguard worker health and recommend workers involved in certain job tasks employ dual hearing protection based on the exposure monitoring results.
Keywords: dosimetry; industrial hygiene; temporary threshold shift; fracking; audiogram; oil and gas extraction